Campur Kode dalam Lagu Jepang Tahun 1990-an dan 2000-an - Ayu Tri Lestari; Arza Aibonotika; Nana Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
ABSTRACTThe research is about English code-mixing in the 1990’s and 2000’sJapanese popular songs lyrics. The question which the study attempts to find answersfor are the following: 1)What is the function of English code-mixing in the 1990’s and2000’s Japanese popular songs lyrics? 2)What is the subject lyrics and song genreeffection the language choice used in the lyrics? This study uses descriptive methodand the applied theory is the English code-mixing function theory of J-pop songlyrics.The result of this study indicates that the main functions of the Englishcode-mixing is intended for prestise and message affirmation conveyed throughrepetition by the singer. Furthermore, it serves to adjust/arrangement of the rhythmtone in the lyrics. Finally it is use to offering alternatives to language use. This studyconcludes the lyrics and genre of the songs have no significant effection the languagechoice used in the lyrics.Keywords: Japanese pop song, code mixing function